CULTIVATION OF HALOPHYTE PLANTS: https://doi.org/10.5281/zenodo.15359818 - Babaniyazov, B.J. (International scientific and practical conference, 2025)
In recent years, the cultivation of halophyte plants has gained significant attention due to their ability to thrive in saline environments. With the increasing salinization of agricultural lands worldwide, halophytes offer a promising alternative for sustainable agriculture. Moreover, these plants contribute to soil reclamation, biofuel production, and food security.This article explores the characteristics, benefits, cultivation techniques, and economic significance of halophyte plants. Additionally, it discusses historical uses, current research, and potential future developments in the field of halophyte farming